Search for t(t)over-bar resonances in highly boosted lepton plus jets and fully hadronic final states in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2017)
A search for the production of heavy resonances decaying into top quark-antiquark pairs is presented. The analysis is performed in the lepton+jets and fully hadronic channels using data collected in proton-proton collisions at root s = 13 TeV using the CMS detector at the LHC, corresponding to an integrated luminosity of 2.6 fb(-1). The selection is optimized for massive resonances, where the top quarks have large Lorentz boosts. No evidence for resonant t (t) over bar production is found in the data, and upper limits on the production cross section of heavy resonances are set. The exclusion limits for resonances with masses above 2 TeV are significantly improved compared to those of previous analyses at root s = 8 TeV.
Keywords: Beyond Standard Model; Hadron-Hadron scattering (experiments); TOP-PAIR; HIERARCHY; TOPCOLOR; DECAY